Science vs social science A study of information-seeking behavior and user perceptions of academic researchers - N.K. Sheeja (Library Review, 2010)
Purpose – The purpose of this paper is to examine the information-seeking behavior of science and social science research scholars, including service effectiveness, satisfaction level on different type of sources and various methods adopted by the scholars for keeping up to date. Design/methodology/approach – Data were gathered using a questionnaire survey of 200, randomly selected, PhD students of science and social science departments of four universities in Kerala, India. Findings – Although similarities exist between social science and science PhD students with regard to information-seeking behavior, there are significant differences as well. There is a significant difference between science and social science scholars on the perception of the adequacy of print journals and database collection which are very relevant to the research purposes. There is no significant difference between science and social science scholars on the perception of the adequacy of e-journals, the most used source for keeping up to date. The study proved that scholars of both the fields are dissatisfied with the effectiveness of the library in keeping them up to date with latest developments. Originality/value – The study is based on actual situation and the result can be used for library service redesign for different types of users.